Criminology Study in Handling Domestic Violence in Sunggal District, Medan City - Muhammad Irwansyah; Junaidi Lubis; Mutmainah Nur Qoiri; Leni Indrayani (The Digest: Journal of Jurisprudence and Legisprudence, 2025)
The case of domestic violence that occurred in Medan Sunggal District, Medan City, is certainly not a new phenomenon in the field of criminology. Along with its development, domestic violence can also be found in various forms of crime, ranging from individual crimes to conventional crimes. The form of domestic violence in criminology research is always related or has a causal relationship with acts of violence. For example, if a husband or wife no longer cares about family life because of the emergence of another ideal figure, communication within the family will decrease. This then triggers excessive suspicion that can lead to domestic violence, such as insulting, mocking, hitting, and so on. The cause of violence, according to positive law, one of which is the existence of a patriarchal culture and the view of society that considers the wife as the property of the husband. Thus, the husband feels fully entitled to his wife and may treat his wife in the way he wants. From an Islamic perspective, this arises due to a lack of piety in individuals, a low understanding of husband-wife relations in the family, and temperamental nature in individuals including committing domestic violence. The effects of criminal acts, especially for those who are victims, are mental disorders. This impact is not only felt by the perpetrators of violence, but also by other family members, especially children. In addition to the effects within the household itself, domestic violence, especially from husband to wife, can also affect the social aspects of life.